BRICS: ACCOMPLISHMENTS AND CHALLENGES OF THE NEW PHASE - V. M. Davidov (Финансы: теория и практика)
The article analyzes the activities of the group of fi ve economies — Brazil, Russia, Indonesia, China, India and South Africa (BRICS). The BRICS integrates fi ve very powerful states; one might even say fi ve civilizations which represent major world nations. It accounts for more than 43 % of the world population and more than 20 % of the global GDP. What is the role of the BRICS? What are its achievements and failures? It’s an open secret that currently the BRICS is going through diffi cult times. Considering BRICS as a new link in global governance implies its institutionalization (in one form or another) at least with a view to interact with other international high level bodies involved in the global governance. The article attempts to analyze the importance of the BRICS for the world community.